2006
DOI: 10.1073/pnas.0511062103
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of adaptor protein 1A coats selectively assembled on liposomes

Abstract: Coat components localize to specific membrane domains, where they sort selected transmembrane proteins. To study how clathrin coats are stabilized on such domains and to identify the protein networks involved, we combined proteomic screens and in vitro liposome-based assays that recapitulate the fidelity of protein sorting in vivo. Our study identifying Ϸ40 proteins on AP-1A-coated liposomes revealed that AP-1A coat assembly triggers the concomitant recruitment of Rac1, its effectors, and the Wave͞Scar complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 53 publications
4
73
0
1
Order By: Relevance
“…Alternatively, AP-1 could also directly contribute to actin organisation: a proteomic analysis showed that several actin nucleators were found on AP-1-enriched liposomes (Baust et al, 2006). We therefore cannot exclude that the loss of AP-1 could also have a direct impact on actin organisation through these actin cofactors, independently of E-cad.…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, AP-1 could also directly contribute to actin organisation: a proteomic analysis showed that several actin nucleators were found on AP-1-enriched liposomes (Baust et al, 2006). We therefore cannot exclude that the loss of AP-1 could also have a direct impact on actin organisation through these actin cofactors, independently of E-cad.…”
Section: Discussionmentioning
confidence: 97%
“…Given that the amino acid sequence of the intracellular tails of all Crb proteins are highly conserved from Drosophila to mammals (Fig. 1A), we incubated mouse Crb2 (mCrb2) tail-coupled liposomes with an adaptor mixture isolated from pig brain (Baust et al, 2006;Crottet et al, 2002). This mixture was highly enriched in constituents of the AP-2 complex (Fig.…”
Section: α-Ada Associates With Crbmentioning
confidence: 99%
“…Interestingly, CDC-42 has been found on AP-1A coated liposomes (Baust et al, 2006), which raises the possibility of a physical interaction between CDC-42 and AP-1, which could be required to prevent or limit CDC-42 basolateral targeting and promote its apical sorting. We propose that by controlling the sorting of both apical and basolateral proteins, including CDC-42 and PAR-6 AP-1 is a crucial factor in apicobasal polarity maintenance, whereas the interactions between AP-1, clathrin and GSL remain to be elucidated.…”
Section: Research Articlementioning
confidence: 99%